THE ROLE OF PARENTS IN NURTURING STUDENTS’ SOCIAL QUOTIENT: CARING - Heri Miarto (STKIP AL HIKMAH SURABAYA, 2025)
This article aims to examine the role of parents in fostering social concern among elementary school children based on literature review from various relevant journals. Social care is a vital character value that should be instilled from an early age, and the family as the first environment plays a key role in shaping children's character. The research method used is a literature review with a descriptive qualitative approach. The findings show that parents play a strategic role in fostering children's caring attitudes through exemplary behavior, communication, habituation of social values, and active involvement in children's social activities. This article also includes a reflection instrument for parents to support implementation at home.